Lay Knowledge About Dementia in Iceland: Symptoms and Risk and Protective Factors - María K. Jónsdóttir PhD; Elva Björk Pálsdóttir BS; Stefanía Ýr Hannesdóttir BS; Thorlakur Karlsson PhD (Gerontology and Geriatric Medicine, 2022)
No studies are available on the lay knowledge about dementia in Nordic countries. A survey was sent to 829 Icelanders aged 25 to 65 (61.2% female). 60.8% resided in the capital area of Reykjavik. About 90% or more recognized eight of eleven dementia symptoms, with females recognizing them proportionally more often than males. About 50% believed that an individual’s risk of developing dementia could be modified. For individual risk factors, agreement ranged from 4% (hearing loss) to 75.1% (history of brain injury). Knowledge about cardiovascular risk factors ranged from 24.8% (obese) to 43.6% (high blood pressure). Participants acknowledged the importance of a healthy diet and an active lifestyle, but only 8% identified a low education level as a risk factor. Public health campaigns and educational efforts about dementia should focus on the whole lifespan targeting all risk and protective factors operating throughout the lifespan.